Does attendance at anatomy practical classes correlate with assessment outcome? A retrospective study of a large cohort of undergraduate anatomy students. Issue 1 (December 2015) - Gonsalvez, David G; Ovens, Matthew; Ivanusic, Jason
Abstract Background Anatomy in medical curricula is typically taught via pedagogy consisting of didactic lectures combined with a practical component. The practical component often includes traditional cadaveric dissection classes and/or workshops utilizing anatomical models, carefully prosected cadaveric material and radiology. The primary aim of this study was to determine if there is an association between attendance at practical classes in anatomy and student assessment outcomes. A secondary aim was to determine if student assessment outcomes were better when students preferentially attended workshops or prosection style practical classes. Method We retrospectively examined practical attendance records and assessment outcomes from a single large anatomy subject (approx. 450 students) to identify how attendance at anatomy practical classes correlates with assessment outcome. Results Students who scored above the median mark for each assessment attended significantly more practical classes than students who scored below the median assessment mark (Mann Whitney;p  < 0.001), and students who attended more than half the practical classes had significantly higher scores on assessments than students that attended less than half the practical classes (Mann Whitney;P  < 0.01). There was a statistically significant positive correlation between attendance at practical classes and outcomes for each assessment (Spearman's correlation;p  < 0.01). There was no difference in assessment outcomes for students who preferentially attended more dissection compared to prosection style classes and vice versa (Mann Whitney;p  > 0.05). Conclusions Our findings show there is an association between student attendance at practical classes and performance on anatomy assessment.